2017
DOI: 10.7150/jca.19601
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and Genomic Variations in Esophageal Squamous Cell Carcinoma: A Review of Technologies, Applications, and Prospections

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common malignant tumors with poor prognosis worldwide. The poor prognosis is due to the advanced stage at the time of diagnosis and the limited clinical staging lacking significant molecular biomarkers to effectively stratify patients for treatment options. As cancer is a disease of genome instability and a resulting of accumulation of genetic alteration, mounting chromosomal and genomic technologies were developed and progressed rapidly which could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Studies on the molecular mechanisms involved in metastasis of ESCC gathered knowledge that it is associated with epithelial to mesenchymal transition (EMT) and EMT‐related genes and proteins . Other studies found that TP53 gene deletion, epidermal growth factor receptor (EGFR) overexpression, integrin α7, and various other mutations and proteins are associated with distant metastasis in ESCC . However, it is yet unknown how the level of expression of these genes and proteins differs between the initially metastatic and recurrent/progressed ESCC after curative treatment, and how they function in each disease group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the molecular mechanisms involved in metastasis of ESCC gathered knowledge that it is associated with epithelial to mesenchymal transition (EMT) and EMT‐related genes and proteins . Other studies found that TP53 gene deletion, epidermal growth factor receptor (EGFR) overexpression, integrin α7, and various other mutations and proteins are associated with distant metastasis in ESCC . However, it is yet unknown how the level of expression of these genes and proteins differs between the initially metastatic and recurrent/progressed ESCC after curative treatment, and how they function in each disease group.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Other studies found that TP53 gene deletion, epidermal growth factor receptor (EGFR) overexpression, integrin 7, and various other mutations and proteins are associated with distant metastasis in ESCC. [28][29][30] However, it is yet unknown how the level of expression of these genes and proteins differs between the initially metastatic and recurrent/progressed ESCC after curative treatment, and how they function in each disease group. Thus, further researches will be needed to evaluate the underlying biology between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…7,22 There are many serological tumor markers in diagnosing and monitoring the malignant tumors. 7,22 There are many serological tumor markers in diagnosing and monitoring the malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, there are many potential risk factors related to ESCC such as alcohol consumption and smoking, high diets in N-nitroso compounds, low in selenium, fungal toxins, highly salted vitamins A and C, and meats zinc. 7 As a result of, the prognosis and hospital medical effect of the patients is not satisfactory. 7 As a result of, the prognosis and hospital medical effect of the patients is not satisfactory.…”
mentioning
confidence: 99%
“…ESCC remains one of the most lethal cancers among all malignancies, with a 5-year survival rate of < 20% once diagnosed [6]. Reasons may be the lack of a sensitive method for early detection; thus, detectable regional and distant metastasis have occurred in most ESCC patients at the time of diagnosis [7,8], and the limited clinical staging criteria lacks signi cant molecular biomarkers to effectively stratify patients for treatment options [9].…”
mentioning
confidence: 99%